Awareness about Mahatma Jyotiba Phule Jan Arogya Yojna among the residential population of an urban community: a cross sectional study - Sapkal, Ashwini B.; Deshpande, Swati (International Journal Of Community Medicine And Public Health, 2019)
Background: The Mahatma Jyotiba Phule Jan Arogya Yojana (MJPJAY) is a unique health insurance scheme which meets the health expenses of the below poverty line / above poverty line families for identified diseases. Lack of awareness regarding the same hinders the beneficiaries from availing the services. Hence studying this and other factors will play an important role in facilitating the access of these beneficiaries to utilize this scheme. Methods: 384 participants were included in the study using proportionate sampling. This is a community based cross sectional study done in the urban field practice area of a tertiary care hospital. Results: 95.57% respondents were having yellow / orange ration card and they were eligible for availing MJPJAY scheme. Awareness about MJPJAY is 51.70% in the age group >55 years. 54.9% of the respondents were aware that the scheme was meant for BPL families while 34.6% respondents did not know about the requirements of the same. Conclusions: Lack of awareness about MJPJAY is the major factor for non-availability of services under this scheme.